Work-life Balance and Burnout on Employee: A Systematic Literature Review and Bibliometric Analysis - Basuni, Basuni; Sopiah, Sopiah (IJBLE Scientific Publications Community Inc., 2023)
The purpose of this literature review was to compile relevant findings from different studies and to investigate the factors that contribute to work life balance and burnout. The method used in this research is the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and Bibliometric analysis using Vos Viewer. Data sources obtained from Scopus for the period 2013-2023. The results of 46 journals were obtained and then data reduction with inclusion and exclusion criteria obtained 6 journals to be reviewed. The results showed an increasing trend of research on work-life balance and burnout and found several topics/keywords that can be used as the basis for further research